Coordination and hydrogen bonded networks featuring 4,4'-dicarboxy-2,2'-bipyridine - Pascual, Eithne Tynan (Trinity College (Dublin, Ireland). School of Chemistry, 2004)
The research presented in this thesis lies within the general area of supramolecular and coordination chemistry. More specifically, this project involves the study of 4,4'-dicarboxy-2,2'-bipyridine (4,4'-H2dcbp) as a linker for the formation of extended networks, either via hydrogen bonding or coordination. Due to the insolubility of 4,4,'-H2dcbp all the reactions within this thesis were carried out under solvothermal conditions, or using a base to deprotonate the ligand under ambient conditions. Paramagnetic metal ions were employed throughout in order to study the 4,4'-dcbp ligand as a propagator of magnetic exchange.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin